Sera of patients with recurrent miscarriages containing anti-trophoblast antibodies (ATAB) reduce hCG and progesterone production in trophoblast cells in vitro. (September 2016) - von Schönfeldt, Viktoria; Rogenhofer, Nina; Ruf, Katharina; Thaler, Christian J.; Jeschke, Udo
Abstract: Problem: Reproductive failure including RM has been suggested to correlate with antibodies that cross react with HLA-negative syncytiotrophoblasts and we have reported that 17% of women with 2 or more miscarriages and 34% of women with 3 or more miscarriages express anti-trophoblast antibodies (ATAB). Until now, the mechanism, how ATAB interfere with pregnancy success is not known. HCG and progesterone both play fundamental roles in supporting human pregnancy. Therefore we investigated the effects of sera of RM patients containing ATAB on the hCG and progesterone production of cells of the choriocarcinoma cell line JEG-3. Method of study: In vitro study to investigate effects of patient sera with and without ATAB on hCG and progesterone secretion of JEG-3 cells. The presence of ATAB was detected as described earlier. Effects of sera from ATAB positive and ATAB negative RM patients on hCG and progesterone secretion by JEG-3 cells were analysed 12 and 24 h after plating. Sera of women without pregnancy pathologies served as controls. Results: Sera of ATAB-positive RM patients significantly inhibit hCG secretion of JEG-3 cells for 12 h after plating compared to sera of healthy controls (p = 0.019) and significantly reduce progesterone production for 12 h (p = 0.046) and 24 h (p = 0.027) of co-culture. Sera of ATAB-negative RM patient show no significant effect on progesterone secretion. Conclusions: Inhibition of hCG and progesterone production might point to a mechanism, how ATAB interfere with early pregnancies.